2007
DOI: 10.1002/jmv.21114
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor is a marker of dysmetabolism in HIV‐infected patients receiving highly active antiretroviral therapy

Abstract: Circulating soluble urokinase plasminogen activator receptor (suPAR) reflects the immune and pro-inflammatory status of the HIV-infected patient. Highly active antiretroviral therapy (HAART) suppresses suPAR. Independent of the immune response to HAART, suPAR remains elevated in some HIV-infected patients, reflecting possibly a low-grade pro-inflammatory state. Low-grade inflammation has been implicated in insulin resistance and other features of dysmetabolism. Accordingly it is hypothesized that circulating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 25 publications
(29 reference statements)
9
125
1
Order By: Relevance
“…suPAR was only moderately correlated with the non-specific inflammatory markers hsCRP and WBC which is consistent with other studies 11,22 In terms of ROC-statistics, suPAR showed somewhat weaker relationships with CVD than hsCRP (0.54 vs 0.57). However, the weak correlation between suPAR and other inflammatory markers suggest that suPAR represents a separate pathway and therefore could add further prognostic information.…”
Section: Discussionsupporting
confidence: 91%
“…suPAR was only moderately correlated with the non-specific inflammatory markers hsCRP and WBC which is consistent with other studies 11,22 In terms of ROC-statistics, suPAR showed somewhat weaker relationships with CVD than hsCRP (0.54 vs 0.57). However, the weak correlation between suPAR and other inflammatory markers suggest that suPAR represents a separate pathway and therefore could add further prognostic information.…”
Section: Discussionsupporting
confidence: 91%
“…Many cytokines and routine laboratory measures were associated with suPAR (Table 2). Convincing correlations between suPAR and the proinflammatory cytokines IL-1 and TNF as well as CRP and creatinine have been shown also in other conditions, 29,[41][42][43] and could be expected since uPAR is up-regulated and shed from immune cells during inflammation. Interestingly, suPAR levels were not inversely associated with complement proteins or complement function, which further demonstrates a lack of apparent association between suPAR and disease activity in lupus.…”
Section: Discussionmentioning
confidence: 70%
“…41 Thus, it is likely that the absence of a general increase in suPAR levels among SLE patients could be a reflection of decreased leukocyte count (Figure 1). Many cytokines and routine laboratory measures were associated with suPAR (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other markers (e.g. CRP), its levels either do not undergo circadian variations at all or they are minimal (assayed each 20 minutes for 24 hours) [67]. Its concentration is stable, even in the case of repeated freezing and thawing of serum samples [68].…”
Section: S Umm Ar Ymentioning
confidence: 99%